Komunikasi dan Hubungan Terapeutik Perawat-Klien terhadap Kecemasan Pra Bedah Mayor - Sri Mulyani, Ira Paramastri, Much. Agus Priyanto (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: A patient who will carry a surgical operation has uncertainty feeling, fear, doubt and anxiety. Anxiety can laid to psychological disruption or functional body disruption of a patient that can affect the surgical operation and anesthesia achievement. Based on pre-research study that has been carried by researcher on June 2007 of 40 patients on in-room at surgery and non-surgery room, it is found that 52,5% at the medium rate of anxiety. By so, we need effective way to decrease anxiety rate of patient. This research is aimed to find the effect of communication and nurse-patient therapeutic relation in decreasing anxiety rate of pre-major surgery patient.Method: Type of the research is experimental quasi with pre-test and post-test group design. The samples of the research consist of 30, that we are given communication treatment and nurse-patient therapeutic relation, and of 30, that we are not given the treatment. The sample is chosen used purposive technique. The technique of collecting data is questionnaire. The data analyzing to know the difference of anxiety with paired samples test, whereas to examine the effect of communication and nurse-patient therapeutic relation with independent samples test with significance rate p=0,05.Result and Discussion: The result of research showed that there is no difference at age characteristics, sex, education, ill period, and marriage status of both group (p>0,05). There is significantly difference anxiety (p<0,05) between the groups. Patients of pre-major surgical operation, that were given therapeutic relation and communication treatment by nurse, have anxiety rate much more lowly why were not given. Test result showed therapeutic relation and communication treatment is carried between nurse and patient can decrease anxiety of pre-major surgical operation with p=0,00 (p<0,05).Conclusion: Therapeutic relation and communication of nurse and patient can decrease anxiety of pre-major surgical operation.Keywords: Therapeutic relation and communication, nurse and client, anxiety, premajor surgical operation